2023
DOI: 10.1177/10815589221141841
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19’s immuno-pathology and cardiovascular diseases

Abstract: The pandemic of COVID-19 in worldwide causes recent millions of morbidity and mortality in all countries and is the most important challenge in the world in recent years. Coronavirus is a single-stranded RNA virus and infection with COVID-19 leads to acute respiratory distress syndrome, lung inflammation, cytokine storm, and death. The other complications include endothelial dysfunction, activation of coagulation, thromboembolic events, and vascular disease. Cardiovascular complications such as myocardial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 121 publications
(233 reference statements)
0
8
0
1
Order By: Relevance
“…Apart from myocardial infarction cardiomyocyte damage may be clinically manifested as myocarditis, cardiomyopathy, and even cardiogenic shock [ 16 ]. Cytokine-induced myocardial cell injury contributes to the activation of heat-shock proteins, leading to further inflammation, mechanical and arrhythmic complications, and cardiomyopathy [ 16 ]. Symptoms related to mechanical and arrhythmic complications include chest pain, dyspnea, and palpitation [ 10 ].…”
Section: Sars-cov-2 and Cardiovascular Inflammationmentioning
confidence: 99%
“…Apart from myocardial infarction cardiomyocyte damage may be clinically manifested as myocarditis, cardiomyopathy, and even cardiogenic shock [ 16 ]. Cytokine-induced myocardial cell injury contributes to the activation of heat-shock proteins, leading to further inflammation, mechanical and arrhythmic complications, and cardiomyopathy [ 16 ]. Symptoms related to mechanical and arrhythmic complications include chest pain, dyspnea, and palpitation [ 10 ].…”
Section: Sars-cov-2 and Cardiovascular Inflammationmentioning
confidence: 99%
“…57 Even today, a relationship between metabolic components and lower plasma NT-proBNP concentration has also been reported. 58,59 Different aetiologies can be considered for the high level of NT-proBNP in patients with fibrillation, such as, first, sometimes the cause of increased NT-proBNP is directly related to immediate hemodynamic changes during AF 60 ; second, high levels of NT-proBNP are sometimes related to chronic structural or functional remodelling of the heart as a result of persistent episodes of AF; and third, an increase in this marker sometimes only indicates that patients with AF have more advanced HF. 12 It is often unclear how elevated NT-proBNP levels in patients with HF and AF should be interpreted.…”
Section: N Terminal Pro Brain Natriuretic Peptide and Brain Natriuret...mentioning
confidence: 99%
“…Various side factors affect the NT‐proBNP serum level, such as age, sex, blood pressure, body mass index, kidney function, and heart rhythm (sinus rhythm vs. AF) 57 . Even today, a relationship between metabolic components and lower plasma NT‐proBNP concentration has also been reported 58,59 …”
Section: N Terminal Pro Brain Natriuretic Peptide and Brain Natriuret...mentioning
confidence: 99%
“…A cohort study found that dyspnea was the most prevalent complaint during hospitalization [ 6 ]. Over the course of the pandemic, reports of multi-organ system involvement during infection have increased, including the cardiovascular and central nervous system (CNS) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic comorbidities such as hypertension have been associated with the severity of cardiac illness [ 8 ]. The mechanisms of cardiac involvement during a COVID-19 infection are not well understood, with studies attributing cardiac injury to the direct SARS-CoV-2 infection of cardiac cells, or myocardial damage developing from an increased metabolic demand due to a systemic infection and ongoing hypoxia [ 9 , 10 , 11 ]. Several case series linked elevated cardiac biomarkers to myocardial injury, leading to a poorer prognosis and increased mortality rate [ 10 ].…”
Section: Introductionmentioning
confidence: 99%